Barriers to and facilitators of active travel from the youth perspective: A qualitative meta-synthesis - Adrian Buttazzoni; Kendra Nelson Ferguson; Jason Gilliland (Elsevier, 2023)
Active travel (AT) such as walking, cycling, or wheeling to/from places represents a relatively accessible form of transportation and source of physical activity for younger populations (ages 5-19). While youth AT is a topic of interest to geography, planning, and public health audiences, larger-scale qualitative reviews of specific topics like in-depth investigations of youth perceived barriers and facilitators of AT have been generally lacking. To offer an original qualitative review of this literature in service of supporting more precise intervention programming and policy recommendations, as well as to outline directions for future research, this paper pairs systematic review and qualitative meta-synthesis methods to document and thematically synthesize the existing qualitative literature regarding youth perceptions of AT barriers and facilitators. After vetting the results of our search, 53 papers met the parameters of the review inclusion criteria and were included in the final meta-synthesis. Using the National Institute for Health and Care Excellence's tool, quality assessments of the 53 included articles suggested, generally, low- to moderate-quality research. Applying qualitative meta-analytical methods, the ensuing developed themes outlined youth perceived barriers as emphasizing social and physical threats, poor motivation and efficacy, and unsupportive local social and community capital. Perceived facilitator themes were characterized by positive individual assessments of AT skill and efficacy, social dynamics, and supportive local community environments. Collectively the generated themes related to perceived barriers and facilitators indicated that factors from across multiple levels (e.g., individual, community) of both social and built environments can be consequential in youth AT decision-making processes and eventual participation, suggesting that future AT interventions should consider multi-level approaches and designs in their programming efforts. Future research is encouraged to undertake sociogeographically comparative or targeted group analyses, explore the inclusion of youth perspectives of, or contributions to, local AT policy, and investigate crucial perceptual mechanisms more in-depth.